Pengaruh Susu Kedelai Terhadap Peningkatan Kadar Hemoglobin Remaja Putri Sma Negeri 1 Perhentian Raja Kampar - Rizki, Nurmalia; Wiji, Rizki Natia; Rismawati, Venny; Harianti, Rini (Jurnal Gizi dan Kuliner, 2022)
Abstract The nutritional problem of adolescent girls is currently getting attention to is anemia (25-40% mild to the severe category of anemia). The study aimed to determine the effect of soy milk on the increase in hemoglobin levels of adolescent girls in SMAN 1 Perhentian Raja. This type of quantitative research is quasi-experimental used a non-equivalent control group design pre-post test. The research was conducted from February to July 2020 at SMA N 1 Perhentian Raja. The sample consisted of 19 students SMA by a stratified random sampling technique. The results showed that subjects had Hb levels of 11-11.9 g/dL, namely 15 people (78.9%), and Hb levels of 8-10.9 g/dL, namely 4 people (21.1%) before consuming soy milk, while the Hb levels of subjects after drinking soy milk had Hb levels of 12.0 g/dL, namely 17 people (89.5%), and Hb levels of 11-11.9 g/dL, namely two people (10.5%).The results of the T-dependent statistical test obtained p-value = 0.000 (p <0.05). It concluded that giving soy milk had a significant effect on the Hb levels of adolescent girls at SMAN 1 Perhentian Raja. It’s hoped that adolescent girls will continue to consume soy milk to maintain normal Hb levels for productivity. Keyword: Hemoglobin Levels, Soymilk, Adolescent Girls